Calibration and Evaluation of GPM Satellite Rainfall for Estimating Annual Maximum Rainfall at Ungauged Sites in the Rea Watershed - I Gusti Ngurah Ketut Udara; Heri Sulistiyono; Hartana (Jurnal Penelitian Pendidikan IPA, 2026)
Limited rain gauge coverage and uneven station distribution remain major challenges for hydrological analysis in ungauged watersheds. This study calibrated and evaluated GPM IMERG satellite rainfall for estimating annual maximum daily rainfall (AMS) in the Rea Watershed, Indonesia. AMS data from four rain gauge stations (Tepas, Taliwang, Seteluk, and Pototano) were used as ground observations, while nine GPM grid cells represented spatial rainfall over the watershed. A rainfall-range-based multiplicative correction was applied using gauge–satellite AMS pairs. Performance was evaluated using Percent Bias (PBIAS), Root Mean Square Error (RMSE), Mean Absolute Error (MAE), and Sum of Squared Errors (SSE), followed by leave-one-station-out (LOSO) validation. Uncorrected GPM data showed systematic underestimation, with PBIAS of -17.7%, RMSE of 66.64 mm, and MAE of 48.67 mm. After optimized correction, PBIAS shifted to +13.8% and MAE slightly improved to 47.97 mm, but RMSE increased to 75.82 mm and SSE to 201,213 mm2. These results indicate that the correction reduced bias but did not improve overall accuracy. LOSO validation produced RMSE values of 50.83-72.13 mm, indicating sensitivity to station omission. Overall, GPM rainfall can support preliminary AMS estimation in ungauged areas, but its application should be treated cautiously because of persistent uncertainty in extreme rainfall estimation.